An Influence: Executive Compensation, Tax Avoidance, and Multiple Large Shareholders (As Moderation) - Chika Aprillia; Budi Supriatono Purnomo (Universitas Pendidikan Indonesia, 2023)
This research is conducted to analyze how executive compensation affects tax avoidance with the presence of multiple large shareholders (MLS) as moderation. This research uses descriptive and verificative methods with a quantitative approach and is conducted on companies engaged in the consumer non-cyclical sector on the IDX in the range of 2019 – 2021. There were as many as 164 total observational data from 68 obtained companies as research samples using purposive sampling techniques. In this research, we found that executive compensation has positive impacts on the practices of corporate tax avoidance. Additionally, it could be moderated by the existence of multiple large shareholders (MLS). MLS moderation can amplify and turn that influence into a negative one. Based on the obtained test results, executive compensation is a monitoring cost incurred to motivate company managers to conduct tax avoidance. Additionally, executive compensation also acts as a reward for additional risks that company managers must face. Companies in the consumer non-cyclical sector were used in this research because of their large numbers and massive contributions to the economy with 2019 – 2021 as a research year due to the COVID-19 outbreak which also impacted the economy.